The Efficacy of Mirabegron as Medical Expulsive Therapy for Distal Ureteral Stones: A Systematic Review and Meta Analysis - I Gede Yogi Prema Ananda; Radika Naufal Hadi Surya; Alfin Putratama; Prima Ardiansah Surya; R. Mohamad Javier; Saidah Rahmat; Eko Setyo Herwanto; Rachmat Budi Prasetyo (East Asian Journal of Multidisciplinary Research, 2023)
The aim of this study was to determine how good mirabegron is as MET for adults with ureteral stones. The study adhered to the 2020 PRISMA guidelines for Systematic Reviews and Meta-Analyses throughout its duration. Four randomized controlled trial (RCT) studies were included in our analysis, encompassing a total of 369 participants. Our meta-analysis findings indicated that individuals who were administered mirabegron exhibited a statistically significant increase in SER [OR = 2.69, 95% CI 1.16-6.23, p = 0.02] and a reduction in the frequency of pain episodes [MD= -0.18, 95% CI -0.33-(-0.04), p = 0.01] in comparison to those receiving a placebo. However, there was no substantial impact of mirabegron on SET [MD= -3.47, 95% CI -8.65-1.72, p = 0.19] when contrasted with the placebo group. Mirabegron exhibited significantly increased SET levels and reduced pain episodes, although it did not have a significant impact on SER.